Students’ Meta-cognitive Strategies for Successful Speech Performance - Auril, Tivinna; Asrida, Deni; Suzanne, Nina; rahmi, Silfia (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study investigates the metacognitive strategies employed by students in managing speech presentations in the Speaking for Argumentative Purposes course at State Islamic University (UIN) Mahmud Yunus Batusangkar. Using a quantitative design, data were collected through a validated 25-item questionnaire administered to 82 fifth- and seventh-semester English Education students in the 2025/2026 academic year. The findings revealed that planning (59.8%) and evaluation (92.7%) were at high levels, while monitoring (52.4%), strategy management and information processing (48.8%), and problem solving (50%) were at medium levels. Evaluation emerged as the most frequently used strategy, indicating strong reflective practices in managing argumentative speech presentations.